2006
DOI: 10.1007/s11144-006-0148-6
|View full text |Cite
|
Sign up to set email alerts
|

Competitive hydrogenation in binary diene systems on a palladium catalyst 

Abstract: Hydrogenations of individual C 5 dienic substrates (1,3-cyclopentadiene, isoprene, 1,4-pentadiene, cis-1,3-pentadiene, trans-1,3-pentadiene) and their binary mixtures on a heterogeneous palladium catalyst were studied in cyclohexane at 25°C and 2 MPa. Selectivities of the competitive hydrogenations were determined and the substrates relative adsorption coefficients calculated. Effects of the diene structure on their reactivity and the stability of the surface complex are discussed. It was found that difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…On the other hand, it was stated that washing the fresh catalyst with benzylamine did not suppress benzyl alcohol formation in the subsequent reaction. From these facts it can be concluded that, in reductive amination of aromatic carbonyl compounds, unsaturated N-containing intermediates, i.e., differently coordinated primary imines and nitrene [6,19,[29][30][31][32][33], adsorb on the Ni catalyst surface stronger than the aldehyde, and thus restrict hydrogenation of the aldehyde to the alcohol (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it was stated that washing the fresh catalyst with benzylamine did not suppress benzyl alcohol formation in the subsequent reaction. From these facts it can be concluded that, in reductive amination of aromatic carbonyl compounds, unsaturated N-containing intermediates, i.e., differently coordinated primary imines and nitrene [6,19,[29][30][31][32][33], adsorb on the Ni catalyst surface stronger than the aldehyde, and thus restrict hydrogenation of the aldehyde to the alcohol (Scheme 4).…”
Section: Resultsmentioning
confidence: 99%
“…Competition of reactants and reaction intermediates for the nickel catalyst surface in benzaldehyde amination. Structure of surface intermediates adapted from studies[6,19,33].…”
mentioning
confidence: 99%
“…While the most studied hydrogenation reactions are the saturation of olefins and aromatics. 51 Hydrocracking and hydrogenation reactions can occur to different extents depending on the operating conditions. At moderate temperature (≤410 °C), hydrogenation reactions dominate, but at high temperature (>410 °C) hydrocracking reactions are predominant.…”
Section: General Aspects Of Slurry-phase Systemsmentioning
confidence: 99%
“…[37,38] In these cases, a variety of transition metals including Co, Ni, Au, Cu, Rh, Pd and Pt have been immobilized on different supports (C, TiO 2 , SiO 4 , Al 2 O 3 and so on), displaying a high potential towards the facile reduction of nitrile/nitro compounds using various reducing agents, such as H 2 , NaBH 4 , N 2 H 4 ⋅H 2 O and so on. [39][40][41][42][43][44][45][46] These catalytic systems constitute a major task for the development of green synthetic methodologies and are of importance in organic chemistry. Recently, extensive studies have been done on the reduction of nitrile/nitro compounds to corresponding amine derivatives using low-cost non-noble metals (e.g.…”
Section: Introductionmentioning
confidence: 99%